Pengaruh Heuristik Bias dengan Mediasi Risk Tolerance dan Financial Literation Serta Inovasi Keuangan Terhadap Keputusan Investasi pada Gen Z - Jane Jacinda Maitri Firman; Liliana Inggrit Wijaya (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to test and analyze the effect of heuristic bias with mediation of risk tolerance and financial literacy and financial innovation on investment decisions in Gen Z. The method in this study is a quantitative method, using primary data obtained through a questionnaire involving 316 respondents as a sample. The Partial Least Square-Structural Equation Model (PLS-SEM) approach was used to analyze the data with JASP software version 0.16.4.0 and SPSS version 29 The results of the study indicate that financial literacy has a significant positive relationship with overconfidence bias, anchoring bias, representativeness bias, availability bias and investment decisions. Then overconfidence bias and risk tolerance have a significant negative relationship with investment decisions. Anchoring bias, availability bias, financial innovation have no significant relationship with investment decisions. Representativeness bias has a significant positive relationship with investment decisions. This study also found that Financial Literacy has a significant positive relationship with risk tolerance.